Sharing Economies, Technologies, and the Changing Nature of Urban Public Space in Medium-Sized Cities (Terr@ Plural, 2019)
Public spaces ensure functional operation and resource sharing in all cities. Streets, squares, and parks afford cultural, socio-economic, and ecological activities benefitting society. However, technology and sharing economies are changing the use of urban spaces. Planners and designers must, therefore, consider the evolution of sharing and other technologies that continue to alter the formation of space in growing medium-sized cities. Public space in a city is a spectrum from the streets to the privacy within homes, and this transect is now being blurred by sharing technology and practices. This paper examines the impact that new technologies and sharing economies have on the way public spaces are generated and used, and what opportunities exist to mitigate negative changes using a human-centered focus and ecological wisdom.